Analisa Peningkatan Kualitas Produk Di CV.XYZ Dengan Menggunakan Metode Six Sigma - Afandi, Nanang Krisna; Sulistiyowati, Wiwik (Universitas Nusantara PGRI Kediri, 2022)
In the competitive industry, quality is a very concern because quality is the central aspect of convincing customers. In this case, the company must be able to provide the best quality for customers. In the company's production process, it is still found that the products produced are not following predetermined specifications. This study aims to determine the value of Sigma and the factors causing damage to the production process. Carrying out quality control is expected to achieve company goals. In this study, the method used in Six Sigma with the stages of define, measure, analyze, improve, and control. The results of Six Sigma are in the form of a company performance baseline at the measurement stage, namely the company in a condition of 3.6 sigma with a DPMO of 17,215.48. The factors that cause product defects are bubble defects on PVC, over glue, scratch, peel-off, and gaps between sides. Suggested improvements to the company are tightening supervision during the production process so that the product conforms to standards and training operators.